An organocatalytic approach to the core of eunicellin. - Gilmour, R; Prior, T; Burton, J; Holmes, AB (2007)
A stereocontrolled synthesis of the core of eunicellin is described featuring a Claisen rearrangement and a diastereoselective organocatalytic Diels-Alder reaction as the key steps.